Manejemen Pemasaran Pendidikan dalam Meningkatkan Kuantitas Peserta Didik - Habiburrachman; Mukhibat (Pascasarjana IAIN Ponorogo, 2024)
This research is motivated by the existence of competition in the world of education that cannot be denied, many educational institutions have been abandoned by their customers and the decline in trust from an educational institution which requires educational institutions to make breakthroughs, especially in marketing management, because marketing management is one of the most important resources. education that is necessary and important to be managed properly and is an inseparable part of education management. This educational marketing management should not be ignored, because with the existence of marketing management it can facilitate the improvement of students in relation to making educational institutions more qualified and qualified. This research uses a qualitative case study approach. With data collection techniques: observation, documentation and in-depth interviews with informants who are considered to have comprehensive knowledge of information related to the research topic being carried out. The purpose of this study was to determine the planning, implementation and evaluation of educational marketing management in increasing the quantity of students carried out at MTs An Nur Mojorejo, Ngraho, Bojonegoro. Based on the research results, the findings obtained are: (1) Education marketing management planning is in accordance with the principles and concepts of strategic management in general, namely internal-external environmental assessment, formulation of vision-mission and work plans which in this case are carried out by way of deliberation/ the meeting which was attended by all elements in MTs An Nur and the An Nur Islamic Boarding School Foundation and was mutually agreed upon. (2) The implementation of educational marketing management uses conventional, modern and door to door strategies and is then regulated through organizing/job descriptions, controlling/supervision systems and meetings to optimize the implementation of educational marketing. (3) Evaluation of educational marketing management to hold deliberations/coordinating meetings on a regular basis as a control and solution in overcoming the obstacles encountered. The meetings held were the first wave meeting and the post-implementation education marketing meeting. This result is to find out how successful the program is running and to achieve the success of educational marketing management.